(untitled) (Academia Science Repository, 2023)
The article highlights the reforms in the field of education in Uzbekistan and the priority tasks of ensuring quality and efficiency in this area. The legal framework for ensuring the effectiveness of the national education system, the priority tasks of the state policy in the field of education are analyzed. From a socio-historical point of view, the process of restoring the status of a teacher in society, achievements in the field of education in the conditions of New Uzbekistan, and the results of reforms in this direction are revealed. The socio-philosophical aspects of best practices, problems and solutions in the field of higher education are highlighted.